Border carbon adjustments for exports of the United States and the European Union: Taking border-crossing frequency into account. (1st September 2017) - Zhang, Zengkai; Zhu, Kunfu
Highlights: Emissions induced by intermediate product trade accounts for a significant share. Multiple rebate revenue reaches 422.14 million dollars. Consumers of China benefit the most from border carbon adjustments for exports. The impact on the electrical equipment sector is more sensitive to border-crossing. The rebate rate should be set lower than the carbon price faced by domestic firms. Abstract: This paper proposes that not only the size and component of carbon footprints are relevant to environmental policies but the border-crossing frequency associated with carbon footprints also has important policy implications, especially given that the fragmentation of production across national boundaries has been developing quickly in recent years. Based on the World Input Output Database, this paper traces carbon transfer along cross-border supply chains and proposes both the upstream and downstream decomposition of export rebates of the United States and the European Union. The carbon transfer from the United States and the European Union to other countries or regions is mainly through international trade in intermediate products, which may cross national borders multiple times. The multiple rebate revenue reaches 422.14 million dollars, and the problem of multiple rebates is much more serious for the sectors with a greater degree of global production fragmentation, such as the electrical and optical equipment sector. In addition, export rebates are mainly targeted at the carbon emissions that are generated in the electricity generation sector and embodied in exports.